Criminal Offense of Narcotics Distribution Through Mass Media - Nimrod Manalu; Fitria Ramadhani Siregar; Rahul Ardian Fikri (CERED Indonesia Institute, 2025)
This research is motivated by the convergence of digital technology disruption, which gave birth to the phenomenon of “Uberization of Drug Trafficking,” and the national criminal law reform through the enactment of Law Number 1 of 2023 concerning the Criminal Code (National Criminal Code). This study aims to analyze the dynamics of narcotics trafficking crimes through mass media ranging from the surface web to the darknet within the new legal framework, as well as to identify potential impunity gaps due to the regulatory transition period. The research method used is normative juridical with statutory, conceptual, and comparative approaches, sourced from secondary data. The results indicate that the shift in the penal paradigm of the National Criminal Code from retributive to rehabilitative and restorative provides a sharp differentiation in handling between abusers and syndicates. However, the revocation of certain lex specialis provisions in the Narcotics Law potentially creates a legal vacuum (rechtsvacuum) regarding electronic transaction offenses if not anticipated with progressive legal interpretation, particularly through the construction of “intermediary tools” and corporate criminal liability. The complexity of modus operandi utilizing end-to-end encryption and cryptocurrency demands a reorientation of law enforcement strategies from conventional approaches towards a Smart Power approach that integrates digital forensics, Artificial Intelligence (AI), and solid international cooperation.